Pedal forces in a simulated 40 km time-trial: preliminar study - Carpes, Felipe Pivetta; Mota, Carlos Bolli; Bini, Rodrigo Rico; Diefenthaeler, Fernando; Guimarães, Antônio Carlos Stringhini; Nabinger, Eduardo (Brazilian journal of physical education and sport, 2005)
The purpose of this study was to analyze the pedal forces during a simulated cycling 40 km time-trial. One experienced triathlete was evaluated using a road bike mounted on a magnetic cycle simulator. The self-preferred cadence and gear was adopted to complete the 40 km in less time possible. The right regular pedal was replaced by an instrumented pedal to record the normal and tangential components of force applied on it. The effective force (perpendicular component to the crank) was calculated from normal and tangential forces. Oxygen uptake, heart rate, power output and speed were registered. During the time-trial the triathlete.s effort increased and this influenced the oxygen uptake and heart rate. The forces magnitude showed a little decreased by the end of the test while the effective force increased on the second half of the recovery phase. Probably the triathlete changed the direction of the forces during the 40 km trial to try to optimize the application of force thus influencing the pedaling technique. The strategy adopted by the triathlete caused a positive change in the pedaling effectiveness.